Factors contributing to the acceptance of Musharakah ( مشاركة ) financing concept by SMEs : a case study of SMEs in Kota Kinabalu City Centre - Rozita @ Uji Mohammed (2011)
This study analyses the banking choice factors, personal factors, and business factors that could have contributed towards the acceptance of the Musharakah financing concept by small and medium-sized enterprises (SMEs). The study chose the SME sector because it is seen by many scholars as a significant market segment for Islamic banks in realizing the aspirations of the government to promote Malaysia as a leading Islamic Financial Centre and to form a strong base for Islamic banking industry capturing 20 per cent market shares of Malaysian financial industry by the year 2010. However, Bank Negara Malaysia (BNM) has found that Malaysian SMEs have not considered Islamic banks as the most desirable financial institutions in terms of seeking financing for their ventures. Many scholars believe that SMEs are depending too much on the conventional short-term financing which can restrict the development of SMEs and the economic growth in the long run. In this study, Musharakah financing concept is being given much emphasis as it has the ability to promote partnerships, banker-partner relationships, and an investment culture between Islamic banks and SMEs. Although it has not been promoted excessively by Islamic banks, particularly at the branch level, its benefits are numerous and undeniable. Throughout the study, four types of analysis namely profile analysis, factor analysis, bivariate analysis, and mean rank analysis were carried out in order to achieve the four main objectives of the study. Based on the first objective, a bivariate analysis was carried out in order to determine factors that contribute towards the acceptance of the Musharakah financing concept by SMEs. The study reveals that out of the 40 independent variables, only 11 were found to have strong relationships with the dependent variable i.e. A18_ACCEPT_CONCEPT. Out of the 11 independent variables, only eight produced significant probability values and thus, could be generalized to population. The second objective then attempted to identify whether there is a ‘finance gap’ within the SME sector. Looking at the profile analysis done on both SME and Islamic bank data, there are approximately about 30 characteristics, which indicate the existence of a finance gap within the SME sector. This gap has created a ‘grey zone’ between the SMEs and Islamic banks, which needs to be properly addressed and eventually bridged if the both parties were to have a banker-partner relationship. The third objective, which concerns the attitude of SMEs towards the Musharakah financing concept, has been met through the profile analysis of SME data. It indicates that the Musharakah financing concept is moderately accepted by the SMEs in Kota Kinabalu City Centre. However, the acceptance level can be enhanced if the SMEs have a better understanding of the concept. The last objective, which aims to determine the extent of the involvement of Islamic banks at the branch level in the Musharakah financing concept, was achieved by performing the profile analysis of Islamic banks. The analysis reveals that there is a low level involvement of Islamic banks in the Musharakah financing concept. Several factors have been identified as the primary causes of this low level involvement and classified as the moderating variables that caused the unpopularity of the Musharakah financing concept within the SME market. In addition, a factor analysis was conducted for the purpose of clustering the 22 banking choice factors into four different groups. Each group shared the same characteristics. This was done to ease the tedious process of interpreting the lengthy list of variables. Finally, conclusions were made according to the desired objectives and several recommendations were proposed in order to improve the current acceptance of the Musharakah financing concept by SMEs and to encourage more active involvement of Islamic banks in promoting the concept as a more Islamic alternative to the conventional banking practices. It is hoped that the study could contribute to the scarce body of knowledge about the selection criteria for specialized financing products and complement previous studies, which have mainly focused on places and individual customers in the Peninsular Malaysia.